PENENTU STRUKTUR MODAL DAN PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Ella Novia Galin; Idamiharti Idamiharti (Jurnal Apresiasi Ekonomi, 2015)
The purposes of this study were to examine the influence of profitability, firm size, growth, asset structure, non debt tax shield on the capital structure and the influence of capital structure on the firm value. The sample used in this research are infrastructure, utility and transportation sector that listed in Indonesia Stock Exchange (ISE) period 2010-2013, which is choosing by purposive sampling method. Testing hypotheses were tested using multiple linear regression. The results showed that only profitability has significant effect on capital structure. Beside that, capital structure also has significant effect on firm value. Keywords : Capital Structure, Firm Value, Profitability, Firm Size, Growth, Asset Structure, Non Debt Tax Shield